Genital Schistosomiasis Leading to Ectopic Pregnancy and Subfertility: A Case for Parasitic Evaluation of Gynaecologic Patients in Schistosomiasis Endemic Areas. (25th July 2013) - Owusu-Bempah, Atta; Odoi, Alexander Tawiah; Dassah, Edward Tieru
Abstract : Female genital schistosomiasis is a significant risk factor for ectopic pregnancy and infertility in schistosomiasis-endemic areas. A case of one previous ectopic pregnancy and subsequent obstruction of the contralateral tube in a secondary subfertility patient with chronic genital schistosomiasis is presented, emphasizing the need for a detailed history and parasitic evaluation of patients presenting with ectopic pregnancy or subfertility in areas where the disease is endemic.